GADAI EMAS DI PERBANKAN SYARIAH - Nursyamsu Nursyamsu (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2016)
Products of Islamic banking is considered to have advantages compared with conventional banking, which is in a range of products sourced from fatwas DSN, considered able to overcome the various problems in the local economy, because much of the element of riba, gharar and gambling and various negative impacts more But in fact the public as customers of Islamic banking is still open to exploitation in various transactions conducted in Islamic banks. Based on the phenomenon that occurs in the community such as the need for pawn gold. Dilakukanlah pelegitimasian law against pledge of gold by the National Islamic Council, at the request of the Islamic banking, which is in the process of establishing such laws, used a variety of approaches, which turned out to give birth to a fatwa that the impact exploit people as customers. From the brief description above, the author will try to discuss a paper on the evaluative analysis DSN No. 26 / DSN-MUI / III / 2002 of gold pawn Islamic bank according to a review of jurisprudence muamalah. National Sharia Council as an institution that fatwa is used as the primary basis of the various products of Islamic banking, have not been able to accommodate emerging models of transactions required by the community such as the need to be pawning gold, which in this case we value such still use classical methods, ie match the reality of the past with the present, which in reality is very much different. Then use a fatwa that emphasizes the benefit. Resulting in the use of multi akad. And causing cracks to appear that could exploit customers. Problems on fatwas born by MUI-DSN, need thorough investigation, even the need for evaluation, especially at the stage of formation fatwa that, in the process of pelegitimasian law against financial transactions contemporary MUI-DSN, preferably involving many parties berkopetensi and experts in their respective fields, so that the later can give birth to a fatwa according to the situation in Indonesia and the Islamic community certainly consistent with Islamic principles